2013
DOI: 10.11648/j.ajls.20130106.15
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multiplex PCR Assay for Detection of Diarrheagenic Escherichia Coli in Street Vended Food Items

Abstract: Pathogenic forms of Escherichia coli are commonly known to cause a variety of diarrheal diseases in hosts.Present study was designed to identify such pathogenic E. coli isolates from 7 different groups of street vended foods including cream, egg, non fried dry food and fried dry food, salad, cooked and non cooked items. Among 400 samples studied, almost all were found to be contaminated with an array of bacteria ranging between 3.24×10 2 -6.5×10 9 cfu/g. Results of multiplex polymerase chain reaction (PCR) ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 22 publications
0
30
0
1
Order By: Relevance
“…Susceptibility of AH 78 strain to 10 different commercially available antibiotic discs (Oxoid); Ceftriazone (30 lg), Gentamycin (10 lg), Nalidixic Acid (30 lg), Ofloxacin (5 lg), Vancomycin (30 lg), Sulfomethoxazole (25 lg), Nitrofurantoin (300 lg), Cephalexin (30 lg), Ampicillin (20 lg) and Doxycycline (30 lg), was interpreted by the disc diffusion method on Mueller-Hinton agar plates following Sarker et al (2013).…”
Section: Antibiotic Sensitivity Testmentioning
confidence: 99%
“…Susceptibility of AH 78 strain to 10 different commercially available antibiotic discs (Oxoid); Ceftriazone (30 lg), Gentamycin (10 lg), Nalidixic Acid (30 lg), Ofloxacin (5 lg), Vancomycin (30 lg), Sulfomethoxazole (25 lg), Nitrofurantoin (300 lg), Cephalexin (30 lg), Ampicillin (20 lg) and Doxycycline (30 lg), was interpreted by the disc diffusion method on Mueller-Hinton agar plates following Sarker et al (2013).…”
Section: Antibiotic Sensitivity Testmentioning
confidence: 99%
“…Significant growth those microorganisms can cause illness in human; others can cause spoilage of food (1). Commencement of enteric diseases (e.g., cholera, diarrhea, dysentery) in the developing countries principally occurs because of microbiologically contaminated food and water associated with unhygienic lifestyle (2,4). In Bangladesh, cholera is a major public health issue due to poor sanitary practices (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…In the field of food microbiology sector in Bangladesh, while lots of works regarding food safety and security issues have been addressed; the specific endogenous oxidative stress ( identification strategy of microbial contaminants in the milk and milk products is still in its infancy (1,8,14,26,(33)(34)(35)(36). Nevertheless, a few earlier researches reported that microbial contamination in milk and milk products could take place from three principal sources: inside the udder; the exterior of the udder and the surface of milk handling; and storage equipment (15,37).…”
Section: Resultsmentioning
confidence: 99%